Low-energy input continuous flow rapid pre-concentration of microalgae through electro-coagulation–flocculation - Shuman, Teodora Rutar; Mason, Gregory; Reeve, Daniel; Schacht, Alexander; Goodrich, Ann; Napan, Katerine; Quinn, Jason (Chemical engineering journal (Lausanne, Switzerland : 1996), 2016)
•ECF uses Ni and Al electrodes and short treatment time, between 0.8 and 7.5s.•Algae rapidly separate from suspension with input energy density of 0.08kWh/m3.•Max separation effectiveness is above 150%/(kWh/m3) obtained at 3.9L/min flow rate.•The ECF processing leaves a large number of viable algal cells, 40–60%.•Metals analysis shows the microalgae sorbs significant amount of metal. This study demonstrates that Nannochloropsis sp. can be effectively pre-concentrated by separation from its growth medium (0.28–0.36g/L) using electro-coagulation–flocculation (ECF) in a continuous flow reactor with both nickel and aluminum electrodes spaced 6.35mm apart. Flow rates studied range between 0.4 and 3.9L/min. Treatment uses energy inputs between 0.08 and 6.43kWh/m3 and voltages between 4 and 20V. This paper describes a novel method that subjects flowing fluid to direct current for a very short time (between 0.8 and 7.5s), upon which algae rapidly separate, approximately 30min after ECF treatment. Fluid flow rate decreases ECF Efficiency as compared to batch tests. Maximum ECF Efficiency recorded in this study was 92% at 0.4L/min and 7V with nickel electrodes. Higher voltage inputs and lower flow rates result in higher ECF Efficiencies. However, the ratio of ECF Efficiency to energy input is the highest for the lowest voltage inputs and highest flow rates. Treatments of 3.9L/min flow rate and 6V resulted in the highest ratio of ECF Efficiency to energy input (151 and 406%/(kWh/m3) for nickel and aluminum electrodes respectively). The ECF processing leaves a large number of viable algal cells that are separated from their growth medium, 40–60% under conditions studied. Metals analysis shows the microalgae, after ECF treatment with nickel and aluminum electrodes at 8V and flow rate of 0.8L/min, sorbs a significant amount of metal, 348.6±66.7mgNi/gdry biomass and 125.2±15.2mgAl/gdry biomass.